OPTIMIZATION OF STATE BUDGET EXPENDITURES IN THE UKRAINE DURING THE WAR TIME (World of finance, 2023)
Introduction. The full-scale military aggression of the Russian Federation against Ukraine led to the destruction of a significant part of Ukraine’s economy and increased the contradictions in the functioning of its financial system. All this led to the need for a systematic analysis of threats and challenges related to the implementation of the budget process from the standpoint of its revenue part, as well as the optimization of expenditures in order to solve the current priorities of ensuring the financing of the Armed Forces and the defense of the state.The purpose of the article is to analyse the dynamics and structure of expenditures of the State Budget of Ukraine and to determine the approaches to their optimization as a necessary condition for the implementation of the priority of ensuring national needs in war conditions.Results. It was emphasized that during the last decade, despite the Russian aggression in 2014, the state budget expenditures did not fully implement the strategic task related to ensuring the defense capability and security of the state. The absence of a budget strategy does not allow to increase the efficiency of the use of state budget expenditures and to minimize the risks and threats that arise in the future. Systematic analysis of budget expenditures over the past 10 years, analysis of changes to the state budget of 2022 and the Law on the State Budget of Ukraine for 2023 made it possible to identify the main contradictions of these processes and justify ways to increase the efficiency of the use of state budget expenditures. Emphasis is placed on the dependence of the State Budget of Ukraine on the financial assistance of our Western partners.Conclusions. The system of operational management of state finances in the context of changes to the State Budget of Ukraine in 2022 became an effective factor in financing the Armed Forces and defense in the first months of the war, and financial assistance from Western partners ensured the relative balance of the State Budget of Ukraine. Financing of defense and security of the state should be a priority of the state’s budget policy both at the level of the Armed Forces and at the level of the defense industry, while constant monitoring of the targeted use of the state’s financial resources is of particular importance.